DETERMINASI HUBUNGAN PENGETAHUAN DEWAN TENTANG ANGGARAN DENGAN PENGAWASAN DEWAN PADA KEUANGAN DAERAH (APBD) (Studi Empiris pada Dewan Perwakilan Rakyat Daerah Provinsi Riau) - Purnomo, Debby; Kurnia, Pipin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study aims to test the relationship determination of the councilorâs knowledge about budget with councilâs oversight upon regional finance (budget). In this study, researchers examined the relationship of councilorâs knowledge about the local finance, on the supervision of local finance as well as using a moderating variable such as accountability, transparency of public policy and community participation and organization commitment, whether it can affect members of the council in monitoring local finances. The problem is whether the council in carrying out its oversight functions over the board due to the knowledge about the budget because council members are generally depart from the political (party) or more caused by other problems. The research sample using purposive sampling which are all members of the provincial council in Riau. The number of respondents of the study was 65 copies, only 55 copies that can be processed. Data analysis was performed using a hypothesis test with the help of SPSS version 20.0. The results proved the relationship between knowledge of the budget with the control panel board in the area affected by the financial accountability, public participation, transparency of public policy and organizational commitment. Therefore this study sported anothetr studies before.Keywords : Accountability, Public Participation, Transparancy in Public Policy, Organizational Commitment, and Financial Control Area (budget)